2007
DOI: 10.1080/14622200701704228
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on lower nitrosamine smokeless tobacco products compared with medicinal nicotine

Abstract: Smokeless tobacco (ST) products have the potential to be used as a harm reduction method for cigarette smokers. These products can deliver significantly less toxicants than cigarettes, although they are not toxicant free nor harmless. It is important to examine potential health risks and benefits of these products. These two small pilot studies examined the effects of two different ST products (Exalt and Ariva) compared with medicinal nicotine, another potential harm reduction product. Dependent, healthy adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…This suggests that Ariva and Stonewall are effective products to curb withdrawal and craving. In support of this interpretation, we found no changes in overall craving or withdrawal as smokers substituted Ariva/ Stonewall for cigarettes, which is generally consistent with reports from others (Blank, Sams, Weaver, & Eissenberg, 2008;Kotlyar et al, 2007;Mendoza-Baumgart et al, 2007). However, although cigarettes per day significantly decreased among smokers who used Ariva/Stonewall, reduction in CO was less striking (6%), suggesting partial compensation (e.g., inhaling deeper, more frequent puffs) and/or problems with the use of CO as a biomarker of tobacco exposure in this population (see following).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This suggests that Ariva and Stonewall are effective products to curb withdrawal and craving. In support of this interpretation, we found no changes in overall craving or withdrawal as smokers substituted Ariva/ Stonewall for cigarettes, which is generally consistent with reports from others (Blank, Sams, Weaver, & Eissenberg, 2008;Kotlyar et al, 2007;Mendoza-Baumgart et al, 2007). However, although cigarettes per day significantly decreased among smokers who used Ariva/Stonewall, reduction in CO was less striking (6%), suggesting partial compensation (e.g., inhaling deeper, more frequent puffs) and/or problems with the use of CO as a biomarker of tobacco exposure in this population (see following).…”
Section: Discussionsupporting
confidence: 81%
“…We further asked PREP participants about the manner in which they used Ariva/Stonewall (e.g., to avoid smoking restrictions, cut down on cigarette smoking). As prior studies have examined toxicant exposure Mendoza-Baumgart et al, 2007), these outcomes were not included here; however, participants provided a breath sample for carbon monoxide (CO) testing at each visit.…”
Section: Assessmentsmentioning
confidence: 99%
“…These studies showed (a) no difference in levels of total NNAL, 1-HOP, and cotinine in smokers of regular, light, and ultra-light cigarettes, respectively, which is consistent with epidemiological studies showing that these cigarettes do not lead to reduced risk for cancer ; (b) significant but only modest reductions in carcinogen exposure when smokers switched from conventional to modified reduced carcinogen cigarettes ( Hatsukami et al, 2004 ); (c) a significant reduction in carcinogens when ST users switched from a conventional U.S. product to Swedish snus (Hatsukami et al) and when smokers switched to Swedish snus or tobacco lozenge ( Mendoza-Baumgart et al, 2007 ); and (d) the greatest reductions occurring with medicinal nicotine products. These studies support the concept of a continuum of risk associated with different types of nicotine-containing products .…”
Section: Key Fi Ndingssupporting
confidence: 72%
“…One group reported that smokers consistently preferred use of nicotine replacement therapy (NRT) over smokeless tobacco, citing such advantages as greater efficacy (17%) and health benefits (13%) (Shiffman et al, 2007). An additional study, which utilized a crossover design (Mendoza-Baumgart et al, 2007), indicated that smokers preferred a nicotine lozenge over the product Exalt, a smokeless product marketed in the United States.…”
Section: Introductionmentioning
confidence: 97%